Structure and dynamics of the insulin receptor: implications for receptor activation and drug discovery. Issue 7 (July 2017) - Ye, Libin; Maji, Suvrajit; Sanghera, Narinder; Gopalasingam, Piraveen; Gorbunov, Evgeniy; Tarasov, Sergey; Epstein, Oleg; Klein-Seetharaman, Judith
Highlights: A review of insulin receptor structural biology. Analysis of insulin receptor interaction with insulin. Interpretation through docking simulations. A new proposed "bow-arrow" model for conformational changes in insulin receptor. Abstract : Recently, major progress has been made in uncovering the mechanisms of how insulin engages its receptor and modulates downstream signal transduction. Here, we present in detail the current structural knowledge surrounding the individual components of the complex, binding sites, and dynamics during the activation process. A novel kinase triggering mechanism, the 'bow-arrow model', is proposed based on current knowledge and computational simulations of this system, in which insulin, after its initial interaction with binding site 1, engages with site 2 between the fibronectin type III (FnIII)-1 and -2 domains, which changes the conformation of FnIII-3 and eventually translates into structural changes across the membrane. This model provides a new perspective on the process of insulin binding to its receptor and, thus, could lead to future novel drug discovery efforts.